Chebyshev Set which Can Be Represented as а Finite Union of Convex Sets - T. A. Zakaryan (ՀՀ ԳԱԱ հրատ.)
We investigate the convexity of Chebyshev sets. It is well known that in a smooth reflexive Banach space with the Kadec-Klee property every weakly closed Chebyshev subset is convex. We prove that the Kadec-Klee property is not required when the Chebyshev set is represented by a finite union of closed convex sets. Մենք հետազոտում ենք չեբիշևյան բազմությունների ուռուցիկությունը: Հայտնի է, որ Կադեց-Կլեե հատկությամբ օժտված ողորկ ռեֆլեքսիվ բանախյան տարածություններում ամեն թույլ փակ չեբիշևյան բազմությունն ուռուցիկ է: Մենք ապացուցում ենք, որ Կադեց-Կլեե հատկությունն անհրաժեշտ չէ, եթե չեբիշևյան բազմությունը փակ ուռուցիկ բազմությունների վերջավոր միավորումն է: Исследована выпуклость чебышевских множеств. Хорошо известно, что в гладких рефлексивных банаховых пространствах, удовлетворяющих свойству Кадеца – Клее, каждое слабо замкнутое чебышевское подмножество является выпуклым. В настоящей статье доказано, что свойство Кадеца – Клее не является необходимым, если чебышевское множество является конечным объединением замкнутых выпуклых множеств.
Keywords: Mathematics; Science